Targeting STAT3 signaling reduces immunosuppressive myeloid cells in head and neck squamous cell carcinoma. (3rd May 2016) - Bu, Lin-Lin; Yu, Guang-Tao; Deng, Wei-Wei; Mao, Liang; Liu, Jian-Feng; Ma, Si-Rui; Fan, Teng-Fei; Hall, Bradford; Kulkarni, Ashok B.; Zhang, Wen-Feng; Sun, Zhi-Jun
ABSTRACT: Cumulative evidence suggests that constitutively activated signal transducer and activator of transcription (STAT3) may contribute to sustaining immunosuppressive status, and that inhibiting STAT3 signaling represents a potential strategy to improve antitumor immunity. In the present study, we observed that high levels phosphorylated of STAT3 are significantly associated with the markers for both myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs) in human head and neck squamous cell carcinoma (HNSCC). Additionally, we showed that targeting STAT3 signaling with a tolerable selective inhibitor S3I-201 significantly decreased immature myeloid cells such as MDSCs, TAMs and iDCs in genetically defined mice HNSCC model. These findings highlight that targeting STAT3 signaling may be effective to enhance antitumor immunity via myeloid suppressor cells in HNSCC.